Analisis Kesulitan Belajar Materi Sejarah Ditinjau dari Faktor Penyebab pada Siswa Kelas VIII di MTsN 3 Blitar - Debby Rofi’ah; Dita Hendriani (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this research is to determine the factors causing learning difficulties experienced by eighth-grade students. This research is motivated by the symptoms that occur in students during history learning. Symptoms often experienced by students include getting bored quickly, difficulty concentrating, laziness, drowsiness, and saturation during history learning. In contrast, only a few students experience learning difficulties in other social studies subjects like economics and geography. This research uses a qualitative approach and descriptive research type. There are three data collection techniques used in this research: observation, interviews, and documentation. Observations are conducted directly by the researcher to obtain valid data. The data analysis technique used includes data condensation, data display, and drawing conclusions.